EFEKTIFITAS BIBLIOTERAPI TERHADAP PENINGKATAN KUALITAS HIDUP PADA PASIEN DENGAN DIABETES MELLITUS PADA KELOMPOK PROLANIS KARTASURA - Martini Listrikawati; Agnes Sri Harti (Universitas Kusuma Husada Surakarta, 2021)
Diabetes Mellitus (DM) is a carbohydrate, protein, and fat metabolism disorder marked with hyperglycemia or blood glucose increase due to an abnormality of insulin secretion or decreased work performance of insulin. One of the handlers of Diabetes Mellitus is exercise. Low impact aerobic gymnastics is a gymnastics with low to moderate intensities, easy-to-do movements, injury-free movements, rhythmic movements, non-jerking movements, and rare sudden movement. Breathing relaxation is a breathing exercise which consists of abdomen breathing and purse lip breathing to reduce stress. The objective of this research is to investigate the effect of low impact aerobic gymnastics and deep breathing relaxation on blood sugar level of the diabetes mellitus elderly at Anggrek Integrated Health Post of Kartasura. This research uses quantitative method with a quasi-experimental research design with a pre-test and post-test approach without control group design. The result of the Wilcoxon’s Test shows that the p-value was 0.000 which was less than 0.05, meaning that the administration of low impact aerobic gymnastics and deep breathing relaxation could reduce the blood sugar level of the diabetes mellitus elderly. Thus, the low impact aerobic gymnastics and deep breathing relaxation had an effect on the blood sugar level of the diabetes mellitus elderly at Anggrek Integrated Health Post of Kartasura.